(untitled) (Razão e Fé, 2023)
The article intends to present the reasons that justify the sanctity of the indigenous Guarani Tiaraju, popularly known as "Sepé Tiaraju". To do so, it uses the complexity of the context of the time, having as a criterion for interpretation the ethical posture in the face of his responsibilities and the price of his defense of the missionary cities, his death in combat. The article places the figure of Tiaraju in the complex and conflictive history of Rio Grande do Sul, and emphasizes the importance, especially for the Catholic Church, of the recognition of his holiness in terms of dignity to the people who keep his memory, the mixed-race people who have much of indigenous heritage, as well as for better treatment of the gaucho culture, overcoming conflicts that may it become a real "model for all the Earth" (Rio Grande do Sul hymn).